Microsoft's Windows Vs Google's Chrome - Who Will Win the Market? - Kaur, Sanjeet; Verma, Sumit Kumar (Indian Journal of Marketing, 2010)
Microsoft has launched its windows 7 in India on 27 October 2009 and approximately 4 months before, Google has also announced to launch a new operating system - Chrome, which will be free to access ,will be free for distribution and use. So who will win the race when the rubber will meet the road ? A few years back, Microsoft introduced windows vista which became a disaster. This time, the fight is between Google and Microsoft because Google is extremely popular among the masses, so this time, the rival is more complaint, but if Microsoft loses again this time, it will put a question mark on Microsoft's existence.